Nickel-based composite thermal spraying coating and preparation method thereof
By using a mixed powder of nickel-plated diamond powder and nickel-based alloy powder in the nickel-based composite coating, a composite coating composed of nickel-chromium alloy phase and diamond with good toughness and high hardness is formed, which solves the problem of insufficient wear resistance of the existing coating in high temperature environments, achieving higher wear resistance and lower maintenance costs.
Patent Information
- Application Number
- CN202510284371.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-05-02
AI Technical Summary
The existing nickel-based composite coatings are prone to thermal damage and uneven distribution of the hard phase in high temperature environments, resulting in limited wear resistance and difficult optimization of process parameters, which affects the bonding strength and porosity of the coating.
The nickel-based diamond powder is used to form a mixed powder and the nickel-based alloy powder is deposited on the surface of the stainless steel workpiece matrix through a high-speed fuel spraying process. The nickel-based alloy powder is wrapped with nickel-plated diamond to form a composite coating composed of nickel-chromium alloy phase and diamond with good toughness.
It improves the density and wear resistance of the coating, extends the service life of the equipment, reduces the overall maintenance cost, and enhances the toughness and hardness of the coating through the selection of nickel-based alloys and the optimization of process parameters.
Smart Images

Figure CN119913448A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal spraying, and in particular relates to a nickel-based composite thermal spraying coating and a preparation method thereof. Background Art
[0002] Nickel-based thermal spray coatings have become one of the most important coatings in the manufacturing industry due to their excellent wear resistance, high hardness and low porosity, especially in the aerospace field, energy field and mechanical equipment manufacturing field.
[0003] In the thermal spraying industry, hard phases are often added to nickel-based coatings to form composite coatings to improve the wear resistance of the coatings. For example, hard particles such as TiB2, WC, and Al2O3 are usually added to nickel-based coatings. However, the wear resistance of such coatings is usually restricted by the following factors. 1) Thermal damage to the hard phase: In the high temperature environment of thermal spraying, hard particles may be thermally damaged, resulting in their decomposition or morphological changes; 2) Uneven distribution of hard phases: Due to differences in physical properties such as wettability, density, and melting point between hard particles and metal substrates, their distribution in the coating may be uneven; 3) Difficulty in optimizing process parameters: There are certain limitations in improving coating performance by adjusting the process parameters of thermal spraying. Changes in these parameters may affect properties such as bonding strength and porosity in the coating; 4) The hardness of the hard phase is low, and in actual service environments, it is scratched by harder hard particles.
[0004] Therefore, the method of adding hard phases such as TiB2, WC, Al2O3 to nickel-based coatings to form composite coatings has limited improvement in wear resistance. For example, in the pump and valve industry, hard particles in the pipeline often scratch the coating surface and cause the coating to wear and fail. This puts higher requirements on the performance of nickel-based composite coatings. How to give the coating better wear resistance without changing the coating preparation method is a problem to be solved. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a nickel-based composite thermal spray coating and a preparation method thereof. A mixed powder is formed by nickel-plated diamond powder and nickel-based alloy powder, and the spray powder is thermally sprayed on the surface of a stainless steel workpiece substrate. During the thermal spraying process, the nickel-based alloy powder wraps the nickel-plated diamond during deposition and is deposited on the surface of the stainless steel workpiece substrate. The composite thermal spray coating is composed of a nickel-chromium alloy phase with good toughness and the hardest diamond in nature. It is easy to fill gaps during deposition, so that the density of the coating is improved, and the composite coating of the nickel-based alloy powder can be given stronger wear resistance, which can greatly improve the service life of the equipment and thus reduce the overall maintenance cost.
[0006] The present invention solves the above technical problems through the following technical solutions.
[0007] One of the purposes of the present invention is to provide a method for preparing a nickel-based composite thermal spray coating, comprising the following steps: S1. Mix nickel-plated diamond powder and nickel-based alloy powder and then ball-mill to obtain spray powder.
[0008] S2. Thermally spraying the spray powder onto the surface of the stainless steel workpiece substrate. During the thermal spraying process, the nickel-based alloy powder wraps the nickel-plated diamond during deposition and is deposited on the surface of the stainless steel workpiece substrate to obtain a nickel-based composite thermal spray coating.
[0009] Furthermore, in the nickel-based composite thermal spray coating, the content of nickel-plated diamond powder is 20 wt.% to 60 wt.%, and the remainder is nickel-based alloy powder, which is 100% in total.
[0010] Furthermore, the nickel-based alloy powder is Ni60 alloy powder.
[0011] Furthermore, the thermal spraying method adopts a high-speed fuel spraying process, the vertical distance between the stainless steel workpiece substrate and the nozzle is 200mm~300mm, the propane gas pressure and the combustion-supporting air pressure are set to 1:1, the pressure is greater than 70 psi~80 psi, the powder feeding gas pressure is 20 psi~22 psi, and the powder feeding speed is 3 g / s~5 g / s.
[0012] Furthermore, the particle size of the nickel-plated diamond powder is 5 μm to 60 μm, and the particle size of the nickel-based alloy powder is 30 μm to 100 μm.
[0013] Furthermore, the stainless steel workpiece substrate is pretreated before thermal spraying, including the following steps: after grinding and smoothing the surface of the stainless steel workpiece substrate, sandblasting is performed to obtain a continuously undulating microscopic morphology structure, wherein the sandblasting medium in the sandblasting process is corundum.
[0014] Furthermore, the rotation speed of the ball mill is 100 r / min to 150 r / min, and the ball milling time is 6 h to 9 h.
[0015] Furthermore, the stainless steel workpiece is 316 stainless steel.
[0016] The second object of the present invention is to provide a nickel-based composite thermal spray coating, which is prepared by the above preparation method. The thickness of the nickel-based composite thermal spray coating is 200 μm to 300 μm, and the porosity of the coating is less than 1.5%.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention forms a mixed powder with nickel-plated diamond powder and nickel-based alloy powder, and thermally sprays the spray powder on the surface of a stainless steel workpiece substrate. During the thermal spraying process, the nickel-based alloy powder wraps the nickel-plated diamond during deposition and is deposited on the surface of the stainless steel workpiece substrate to prevent the nickel-plated diamond from falling off. The mixed powder is easy to fill gaps when deposited by thermal spraying to form a nickel-based composite thermal spray coating, thereby improving the density of the coating. The nickel-based composite thermal spray coating is composed of a nickel-chromium alloy phase with good toughness and the hardest diamond in nature, which can give the nickel-based alloy powder composite coating a stronger wear resistance, greatly improve the service life of the equipment, and thus reduce the overall maintenance cost.
[0018] (2) The present invention adopts Ni60 alloy powder as the nickel-based alloy powder. The Ni60 alloy powder has good self-fluxing property and can well wrap the nickel-plated diamond deposition through thermal spraying. In addition, a layer of nickel is plated on the surface of the Ni60 alloy powder. While protecting the diamond from thermal damage during deposition, it is easier for the Ni60 particles to wrap the nickel-plated diamond during deposition, preventing the nickel-plated diamond from falling off, making it easier to fill gaps during the deposition of the mixed powder, and improving the density of the coating. The Ni60 alloy has the characteristics of good toughness and high hardness, and can well hold the diamond particles. In addition, a layer of nickel is plated on the surface of the diamond. While protecting the diamond from thermal damage during deposition, it is easier for the Ni60 particles to wrap the nickel-plated diamond during deposition.
[0019] (3) The present invention uses a high-speed air-fuel spraying technology that is more advanced than supersonic flame spraying to deposit a layer of super wear-resistant coating containing diamond on a 316 stainless steel substrate. High-speed air-fuel spraying technology not only has good cost advantages, but also has higher deposition efficiency and spraying speed. The prepared nickel-based composite thermal spray coating has better wear resistance than Ni60 thermal spray coating and can be used on the surface of coal chemical slag lock valves to effectively resist scratches on the sealing surface by hard particles, thereby reducing the maintenance cost of the overall equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the structure of the nickel-based composite thermal spray coating of the present invention.
[0021] Figure 2 This is a surface morphology image of the nickel-based composite thermal spray coating prepared in Example 1 of the present invention under a light microscope.
[0022] Figure 3 The scanning electron microscope image of the sprayed powder of Example 1 of the present invention and the cross-sectional scanning electron microscope image of the prepared nickel-based composite thermal spray coating are shown in FIG. Figure 3 In the figure, a is the electron microscope morphology of the composite powder, and b is the scanning electron microscope image of the coating cross section.
[0023] Figure 4The following are scanning electron micrographs of the sprayed powder of Example 2 of the present invention and a cross-sectional scanning electron micrograph of the prepared nickel-based composite thermal spray coating. Figure 4 In the figure, a is the electron microscope morphology of the composite powder, and b is the scanning electron microscope image of the coating cross section.
[0024] Figure 5 The following are scanning electron micrographs of the sprayed powder of Example 4 of the present invention and a cross-sectional scanning electron micrograph of the prepared nickel-based composite thermal spray coating. Figure 5 In the figure, a is the electron microscope morphology of the composite powder, and b is the scanning electron microscope image of the coating cross section.
[0025] Figure 6 This is a friction coefficient curve of the thermal spray coating prepared in Examples 1 to 3 of the present invention and Comparative Example 1.
[0026] Figure 7 This is a diagram showing the wear amount of thermal spray coatings prepared in Examples 1 to 3 of the present invention and Comparative Example 1.
[0027] Figure 8 This is a friction coefficient curve of the thermal spray coating prepared in Examples 3 to 5 of the present invention and Comparative Example 1.
[0028] Fig. 9 This is a diagram showing the wear amount of thermal spray coatings prepared in Examples 3 to 5 of the present invention and Comparative Example 1.
[0029] Fig.10 This is a graph of the median particle size of nickel-plated diamonds in Examples 1 to 3 of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0032] The method of adding hard phases such as TiB2, WC, Al2O3 to the existing nickel-based coating to form a composite coating has limited improvement in wear resistance. For example, in the pump and valve industry, hard particles in the pipeline often scratch the coating surface and cause the coating to wear and fail. This puts higher requirements on the performance of nickel-based composite coatings. How to give the coating better wear resistance without changing the coating preparation method is a problem to be solved.
[0033] Based on the above problems, the present invention adds the hardest diamond in nature to the nickel-based coating, uses diamond with nickel plating to prevent its thermal damage at high temperature, and considers the wetting problem between the hard particles and the metal matrix, and uses nickel-based alloy powder with stronger wetting performance as the nickel-based metal in the composite coating. A method for preparing a nickel-based composite thermal spray coating is provided, comprising the following steps:
[0034] S1. Mix nickel-plated diamond powder and nickel-based alloy powder and then ball-mill to obtain spray powder.
[0035] S2. Thermally spraying the spray powder onto the surface of the stainless steel workpiece substrate. During the thermal spraying process, the nickel-based alloy powder wraps the nickel-plated diamond during deposition and is deposited on the surface of the stainless steel workpiece substrate to obtain a nickel-based composite thermal spray coating.
[0036] The present invention uses nickel-plated diamond powder and nickel-based alloy powder to form a mixed powder, and thermally sprays the spray powder on the surface of a stainless steel workpiece substrate. During the thermal spraying process, the nickel-based alloy powder wraps the nickel-plated diamond during deposition and is deposited on the surface of the stainless steel workpiece substrate, forming a nickel-chromium alloy phase with good toughness and the hardest diamond composition in nature. It is easy to fill gaps during deposition, which improves the density of the coating and can give the Ni60 composite coating stronger wear resistance, which can greatly increase the service life of the equipment and reduce the overall maintenance cost. The schematic diagram of the structure of the prepared nickel-based composite thermal spray coating is shown in the figure. Figure 1 As shown, a is the Ni60 phase in the composite coating; b is the diamond in the composite coating; c is the nickel plating on the surface of the diamond; and d is the stainless steel substrate.
[0037] In a specific embodiment, the content of nickel-plated diamond powder in the spray powder is 20 wt.% to 60 wt.%, and the balance is nickel-based alloy powder, which is 100% in total. In the present invention, in a certain content range of nickel-plated diamond, there is enough nickel-based alloy to hold the diamond particles and play the role of diamond reinforcement phase to a certain extent. Adding 20wt.% diamond can significantly improve the wear resistance of the coating. As the diamond content increases, the wear resistance of the coating gradually increases, and the phenomenon of diamond falling off from the coating is more, which can still provide considerable wear resistance, but when the content of nickel-plated diamond powder in the spray powder exceeds 60wt.%, its wear resistance decreases; the nickel-based alloy powder wraps the nickel-plated diamond and deposits on the surface of the stainless steel workpiece substrate during deposition. A certain content of diamond can provide sufficient strength, and the surrounding tissue can provide a certain holding force to prevent the diamond from falling off. It is easy to fill the gap during deposition, so that the density of the coating is improved, and the composite coating can be given stronger wear resistance.
[0038] In a specific embodiment, the nickel-based alloy powder is Ni60 alloy powder. The present invention uses Ni60 alloy powder as the nickel-based alloy powder. Ni60 alloy powder has good self-fluxing property and can well wrap nickel-plated diamond deposition through thermal spraying. The diamond surface is plated with a layer of nickel. While protecting the diamond from thermal damage during deposition, it is easier for Ni60 particles to wrap the nickel-plated diamond during deposition to prevent the nickel-plated diamond from falling off. It is easy to fill gaps during deposition, so that the density of the coating is improved. Ni60 alloy has the characteristics of good toughness and high hardness, and can well hold diamond particles. In the present invention, an alloy with a lower melting point than Ni60 can also be used.
[0039] In a specific embodiment, the thermal spraying method adopts a high-speed fuel spraying process, the vertical distance between the stainless steel workpiece substrate and the nozzle is 200 mm to 300 mm, the propane gas pressure and the combustion-supporting air pressure are set to 1:1, the pressure is 70 ps to 80 psi, the powder feeding pressure is 20 ps to 22 psi, and the powder feeding speed is 3 g / s to 5 g / s. In the present invention, during thermal spraying, the sample surface is first preheated with a supersonic flame, and when the temperature reaches the preheating temperature, the preheating temperature is set to 200°C to 300°C; the process parameters of the high-speed fuel spraying process are based on the spraying equipment provided by the KERMETICO equipment manufacturer, and are set according to the HVAF high-speed fuel spraying system, and the computer-aided manufacturing program is started. According to the shape of the prepared sample, the supersonic flame nozzle is made to follow a certain feed trajectory to deposit a layer of nickel-based diamond composite coating on the sample surface. The present invention uses a more advanced high-speed air fuel spraying technology than supersonic flame spraying to deposit a layer of super wear-resistant coating containing diamond on the stainless steel substrate. High velocity air fuel spray technology not only has good cost advantages, but also has higher deposition efficiency and spraying speed.
[0040] In a specific embodiment, the particle size of the nickel-plated diamond powder is 5 μm to 60 μm, and the particle size of the nickel-based alloy powder is 30 μm to 100 μm. In the present invention, if the particle size of the nickel-plated diamond powder and the nickel-based alloy powder is too large, the structure in the middle of the particle cannot reach the alloy melting point or even the strong plastic deformation temperature in the spraying system (effective mechanical bite cannot be formed between the deposited powder particles); if the particle size is too small, the particle is easy to form nodules in the nozzle.
[0041] In a specific embodiment, the stainless steel workpiece substrate is pretreated before thermal spraying, including the following steps: after the surface of the stainless steel workpiece substrate is polished and flattened, sandblasting is performed to obtain a continuously undulating microscopic morphology structure, wherein the sandblasting medium during the sandblasting process is corundum, and the particle size of the corundum is 650 μm to 750 μm. After the sandblasting is completed, acetone is used to wash away the oil on the surface of the sample, and then deionized water is used in an ultrasonic cleaning machine to wash away the acetone and the corundum attached to the surface of the sample; finally, it is placed in a drying box for standby use.
[0042] In a specific embodiment, the rotation speed of the ball mill is 100 r / min to 150 r / min, and the powder mixing time is 6 h to 9 h. In the present invention, the purpose of the ball mill is to crush and evenly mix the nickel-plated diamond powder and the nickel-based alloy powder.
[0043] In a specific embodiment, the stainless steel workpiece is 316 stainless steel. In the present invention, the stainless steel workpiece may also be other stainless steel workpieces other than 316 stainless steel. The present invention selects 316 stainless steel mainly to illustrate the performance of the super wear-resistant coating containing diamond.
[0044] In addition, the present invention also provides a nickel-based composite thermal spray coating, which is prepared by the above-mentioned preparation method. The thickness of the nickel-based composite thermal spray coating is 200 μm to 300 μm, and the coating porosity is less than 1.5%. The present invention prepares a layer of nickel-based diamond composite coating on stainless steel, and uses a high-speed air-fuel spray system to deposit Ni60 powder with good self-fluxing property and nickel-plated diamond on the stainless steel substrate, thereby giving the coating extremely high wear resistance, which can greatly improve the service life of the equipment and thus reduce the overall maintenance cost. When the thickness of the nickel-based composite thermal spray coating is too low, it cannot provide sufficient processing allowance; if the thickness is too thick, it will greatly increase the processing cost.
[0045] The invention is further described below through specific examples.
[0046] Example 1 A method for preparing a nickel-based composite thermal spray coating comprises the following steps: S1. Select Ni60 powder with a particle size of D50≈35 μm and nickel-plated diamond powder with a particle size of D50≈50 μm as spray powders. The mass fraction of nickel-plated diamond powder in the spray powder is 37.5 wt.%; place the spray powder in a planetary ball mill for ball milling. The ball milling parameters are: 120 r / min, 8 h. After the ball mill finishes mixing the powder, mix it evenly and pour it into a bottle for use. Put it in a drying oven to remove water vapor in the powder before spraying.
[0047] S2. Select a 5 mm thick 316L austenitic stainless steel sheet, grind the surface of the stainless steel sheet flat with a precision grinder, cut it into 5 cm × 5 cm square test blocks by wire cutting according to the test requirements, and use corundum as the sandblasting medium to perform sandblasting to obtain a continuously undulating microscopic morphology structure, then clean the surface dust and stains such as oxide scale; use acetone to wash off the oil on the surface of the sample, and then use deionized water in an ultrasonic cleaner to wash off the attached reagents and corundum particles; finally, put it in a drying oven to remove the surface moisture to obtain a 316 stainless steel workpiece matrix.
[0048] S3. Place the 316 stainless steel workpiece substrate on the workbench, use the high-speed fuel spray (HVAF) system of KERMETICO, USA, and connect propane and compressed air. The gas input pressures are 76.5 psi and 78.4 psi respectively. Then ignite the combustion chamber, and the flame flows through the Laval nozzle to accelerate to supersonic speed; control the spray flame to be perpendicular to the surface of the stainless steel workpiece substrate, the vertical distance is 200 mm, and feed according to a certain trajectory to cover the surface of the sample, and preheat the surface of the sample with a supersonic flame; use an infrared thermometer to measure the temperature of the sample surface. After reaching 300°C, introduce powder feeding gas, and set the powder feeding speed to 3 g / s. Start the instructions in the CAM processing program to make the powder evenly deposited on the 316 stainless steel workpiece substrate to obtain a nickel-based composite thermal spray coating.
[0049] Example 2 A method for preparing a nickel-based composite thermal spray coating comprises the following steps: S1. Select Ni60 powder with a particle size of D50≈35 μm and nickel-plated diamond powder with a particle size of D50≈10 μm as spray powders. The mass fraction of nickel-plated diamond powder in the spray powder is 37.5 wt.%; place the spray powder in a planetary ball mill for ball mill mixing. The ball milling parameters are: 120 r / min, 8 h. After the ball mill mixing is completed, mix evenly and pour into a bottle for use. Put it in a drying oven to remove water vapor in the powder before spraying.
[0050] S2. Select a 5 mm thick 316L austenitic stainless steel sheet, grind the surface of the stainless steel sheet flat with a precision grinder, cut it into 5 cm × 5 cm square test blocks by wire cutting according to the test requirements, and use corundum as the sandblasting medium to perform sandblasting to obtain a continuously undulating microscopic morphology structure, then clean the surface dust and stains such as oxide scale; use acetone to wash off the oil on the surface of the sample, and then use deionized water in an ultrasonic cleaner to wash off the attached reagents and corundum particles; finally, put it in a drying oven to remove the surface moisture to obtain a 316 stainless steel workpiece matrix.
[0051] S3. Place the 316 stainless steel workpiece substrate on the workbench, use the high velocity fuel spray (HVAF) system of KERMETICO, USA, and connect propane and compressed air. The gas input pressures are 76.5psi and 78.4psi respectively. Then the combustion chamber is ignited, and the flame is accelerated to supersonic speed through the Laval nozzle. The spraying flame is controlled to be perpendicular to the surface of the stainless steel workpiece substrate, with a vertical distance of 200 mm, and is fed along a certain trajectory to cover the surface of the sample. The surface of the sample is preheated with a supersonic flame. The temperature of the sample surface is measured with an infrared thermometer. After reaching 300°C, powder feeding gas is introduced, and the powder feeding speed is set to 3 g / s. The instructions in the CAM processing program are started to make the powder evenly deposited on the 316 stainless steel workpiece substrate to obtain a nickel-based composite thermal spray coating.
[0052] Example 3 A method for preparing a nickel-based composite thermal spray coating comprises the following steps: S1. Select Ni60 powder with a particle size of D50≈35 μm and nickel-plated diamond powder with a particle size of D50≈30 μm as spray powders. The mass fraction of nickel-plated diamond powder in the spray powder is 37.5 wt.%; place the spray powder in a planetary ball mill for ball mill mixing. The ball milling parameters are: 120 r / min, 8 h. After the ball mill mixing is completed, mix evenly and pour into a bottle for use. Put it in a drying oven to remove water vapor in the powder before spraying.
[0053] S2. Select a 5 mm thick 316L austenitic stainless steel sheet, grind the surface of the stainless steel sheet flat with a precision grinder, cut it into 5 cm × 5 cm square test blocks by wire cutting according to the test requirements, and use corundum as the sandblasting medium to perform sandblasting to obtain a continuously undulating microscopic morphology structure, then clean the surface dust and stains such as oxide scale; use acetone to wash off the oil on the surface of the sample, and then use deionized water in an ultrasonic cleaner to wash off the attached reagents and corundum particles; finally, put it in a drying oven to remove the surface moisture to obtain a 316 stainless steel workpiece matrix.
[0054] S3. Place the 316 stainless steel workpiece substrate on the workbench, use the high-speed fuel spray (HVAF) system of KERMETICO, USA, and connect propane and compressed air. The gas input pressures are 76.5 psi and 78.4 psi respectively. Then ignite the combustion chamber, and the flame flows through the Laval nozzle to accelerate to supersonic speed; control the spray flame to be perpendicular to the surface of the stainless steel workpiece substrate, the vertical distance is 200 mm, and feed according to a certain trajectory to cover the surface of the sample, and preheat the surface of the sample with a supersonic flame; use an infrared thermometer to measure the temperature of the sample surface. After reaching 300°C, introduce powder feeding gas, and set the powder feeding speed to 3 g / s. Start the instructions in the CAM processing program to make the powder evenly deposited on the 316 stainless steel workpiece substrate to obtain a nickel-based composite thermal spray coating.
[0055] Example 4 A method for preparing a nickel-based composite thermal spray coating comprises the following steps: S1. Select Ni60 powder with a particle size of D50≈35 μm and nickel-plated diamond powder with a particle size of D50≈50 μm as spray powders. The mass fraction of nickel-plated diamond powder in the spray powder is 25 wt.%; place the spray powder in a planetary ball mill for ball mill mixing. The ball milling parameters are: 120 r / min, 8 h. After the ball mill mixing is completed, mix evenly and pour into a bottle for use. Put it in a drying oven to remove water vapor in the powder before spraying.
[0056] S2. Select a 5 mm thick 316L austenitic stainless steel sheet, grind the surface of the stainless steel sheet flat with a precision grinder, cut it into 5 cm × 5 cm square test blocks by wire cutting according to the test requirements, and use corundum as the sandblasting medium to perform sandblasting to obtain a continuously undulating microscopic morphology structure, then clean the surface dust and stains such as oxide scale; use acetone to wash off the oil on the surface of the sample, and then use deionized water in an ultrasonic cleaner to wash off the attached reagents and corundum particles; finally, put it in a drying oven to remove the surface moisture to obtain a 316 stainless steel workpiece matrix.
[0057] S3. Place the 316 stainless steel workpiece substrate on the workbench, use the high-speed fuel spray (HVAF) system of KERMETICO, USA, and connect propane and compressed air. The gas input pressures are 76.5 psi and 78.4 psi respectively. Then ignite the combustion chamber, and the flame flows through the Laval nozzle to accelerate to supersonic speed; control the spray flame to be perpendicular to the surface of the stainless steel workpiece substrate, the vertical distance is 200 mm, and feed according to a certain trajectory to cover the surface of the sample, and preheat the surface of the sample with a supersonic flame; use an infrared thermometer to measure the temperature of the sample surface. After reaching 300°C, introduce powder feeding gas, and set the powder feeding speed to 3 g / s. Start the instructions in the CAM processing program to make the powder evenly deposited on the 316 stainless steel workpiece substrate to obtain a nickel-based composite thermal spray coating.
[0058] Example 5 A method for preparing a nickel-based composite thermal spray coating comprises the following steps: S1. Select Ni60 powder with a particle size of D50≈35 μm and nickel-plated diamond powder with a particle size of D50≈30 μm as spray powders. The mass fraction of nickel-plated diamond powder in the spray powder is 50 wt.%; place the spray powder in a planetary mill and mix it in a ball mill. The ball milling parameters are: 120 r / min, 8 h. After the ball mill mixing is completed, mix evenly and pour it into a bottle for use. Put it in a drying oven to remove water vapor in the powder before spraying.
[0059] S2. Select a 5 mm thick 316L austenitic stainless steel sheet, grind the surface of the stainless steel sheet flat with a precision grinder, cut it into 5 cm × 5 cm square test blocks by wire cutting according to the test requirements, and use corundum as the sandblasting medium to perform sandblasting to obtain a continuously undulating microscopic morphology structure, then clean the surface dust and stains such as oxide scale; use acetone to wash off the oil on the surface of the sample, and then use deionized water in an ultrasonic cleaner to wash off the attached reagents and corundum particles; finally, put it in a drying oven to remove the surface moisture to obtain a 316 stainless steel workpiece matrix.
[0060] S3. Place the 316 stainless steel workpiece substrate on the workbench, use the high-speed fuel spray (HVAF) system of KERMETICO, USA, and connect propane and compressed air. The gas input pressures are 76.5 psi and 78.4 psi respectively. Then ignite the combustion chamber, and the flame flows through the Laval nozzle to accelerate to supersonic speed; control the spray flame to be perpendicular to the surface of the stainless steel workpiece substrate, the vertical distance is 200 mm, and feed according to a certain trajectory to cover the surface of the sample, and preheat the surface of the sample with a supersonic flame; use an infrared thermometer to measure the temperature of the sample surface. After reaching 300°C, introduce powder feeding gas, and set the powder feeding speed to 3 g / s. Start the instructions in the CAM processing program to make the powder evenly deposited on the 316 stainless steel workpiece substrate to obtain a nickel-based composite thermal spray coating.
[0061] Comparative Example 1 A method for preparing a thermal spray coating comprises the following steps: S1. Select Ni60 powder with a particle size of D50≈35 μm as the spray powder; place the spray powder in a planetary ball mill for ball mill mixing. The ball milling parameters are: 120 r / min, 8 h. After the ball mill mixing is completed, pour the mixture into a bottle for later use after mixing evenly. Place the powder in a drying oven to remove moisture from the powder before spraying.
[0062] S2. Select a 5 mm thick 316L austenitic stainless steel sheet, grind the surface of the stainless steel sheet flat with a precision grinder, cut it into 5 cm × 5 cm square test blocks by wire cutting according to the test requirements, and use corundum as the sandblasting medium to perform sandblasting to obtain a continuously undulating microscopic morphology structure, then clean the surface dust and stains such as oxide scale; use acetone to wash off the oil on the surface of the sample, and then use deionized water in an ultrasonic cleaner to wash off the attached reagents and corundum particles; finally, put it in a drying oven to remove the surface moisture to obtain a 316 stainless steel workpiece matrix.
[0063] S3. Place the 316 stainless steel workpiece substrate on the workbench, use the high velocity fuel spray (HVAF) system of KERMETICO, USA, and connect propane and compressed air. The gas input pressures are 76.5 psi and 78.4 psi respectively. Then the combustion chamber is ignited, and the flame is accelerated to supersonic speed through the Laval nozzle. The spraying flame is controlled to be perpendicular to the surface of the stainless steel workpiece substrate, with a vertical distance of 200 mm, and is fed along a certain trajectory to cover the surface of the sample. The surface of the sample is preheated with a supersonic flame. The temperature of the sample surface is measured with an infrared thermometer. When it reaches 300°C, powder feeding gas is introduced, and the powder feeding speed is set to 3 g / s. The instructions in the CAM processing program are started to make the powder evenly deposited on the 316 stainless steel workpiece substrate to obtain a thermal spray coating.
[0064] The samples prepared in Examples 1 to 5 and Comparative Example 1 were cut into 10 mm × 10 mm sizes using wire cutting, and the sprayed surfaces of the samples were polished and leveled using 240#, 400#, 800#, 1200#, and 1500# water-abrasive sandpapers in sequence. The samples were then polished to a bright finish using a polishing machine and performance tests were performed.
[0065] Figure 2 This is a surface morphology of the nickel-based composite thermal spray coating prepared in Example 1 of the present invention under a light microscope. Figure 2 As shown, the diamond is well deposited and evenly distributed in the coating.
[0066] Figure 3 The scanning electron microscope image of the sprayed powder of Example 1 of the present invention and the cross-sectional scanning electron microscope image of the prepared nickel-based composite thermal spray coating are shown in FIG. Figure 3 a in the figure is the electron microscope morphology of the composite powder, and b is the scanning electron microscope image of the coating cross section. Figure 3 As shown in a, the spherical or nearly spherical ones are Ni60 alloy powders, and the irregular blocks are nickel-plated diamonds; Figure 3 As shown in b, the diamond is well deposited and evenly distributed in the coating, accompanied by a small amount of diamond breakage.
[0067] Figure 4 The following are scanning electron micrographs of the sprayed powder of Example 2 of the present invention and a cross-sectional scanning electron micrograph of the prepared nickel-based composite thermal spray coating. Figure 4 a in the figure is the electron microscope morphology of the composite powder, and b is the scanning electron microscope image of the coating cross section. Figure 4 As shown in a, the spherical or nearly spherical ones are Ni60 alloy powders, and the irregular blocks are nickel-plated diamonds; Figure 4 As shown in b, the diamond is well deposited and distributed evenly in the coating.
[0068] Figure 5 The following are scanning electron micrographs of the sprayed powder of Example 4 of the present invention and a cross-sectional scanning electron micrograph of the prepared nickel-based composite thermal spray coating. Figure 5 a in the figure is the electron microscope morphology of the composite powder, and b is the scanning electron microscope image of the coating cross section. Figure 5 As shown in a, the spherical or nearly spherical ones are Ni60 alloy powders, and the irregular blocks are nickel-plated diamonds; Figure 5 As shown in b, the diamond deposition is poor and the distribution in the coating is uneven
[0069] The wear resistance test of the samples prepared in Examples 1 to 5 and Comparative Example 1 was performed, comprising the following steps: The reciprocating friction and wear test of different coatings was carried out by using MS-M9000 multifunctional friction tester: the test parameters were set as follows: load 20 N; aluminum oxide was selected as the grinding ball, and the grinding ball had a diameter of 6 mm; the reciprocating displacement was set to 5 mm; the frequency was 2 Hz; the test time was 1 h. The mass loss of the sample was calculated by weighing the mass of the sample before and after the wear test.
[0070] Figure 6 The friction coefficient curve of the thermal spray coating prepared in Examples 1 to 3 of the present invention and Comparative Example 1 is shown. Figure 6 As shown in the figure, the friction coefficient curves of the composite coatings doped with diamond are smaller than that of the pure Ni60 coating, and the composite coatings doped with 10 μm and 50 μm particles show a friction reduction trend on the curves.
[0071] Figure 7 The figure is a diagram showing the wear amount of the thermal spray coating prepared in Examples 1 to 3 of the present invention and Comparative Example 1. Figure 7 As shown in the figure, in terms of wear loss, when the nickel-plated diamond content is 37.5 wt.%, the wear loss of nickel-plated diamond with a particle size of 50 μm is much lower than that of other coatings.
[0072] Figure 8 The friction coefficient curve of the thermal spray coating prepared in Examples 3 to 5 of the present invention and Comparative Example 1 is shown. Figure 8 As shown, 25.0 wt.%, 37.5 wt.% and 50.0 wt.% all exhibit a wear-reducing trend, and the friction coefficient curve of the 50 wt.% coating is lower than 0.05 at 60 min.
[0073] Fig. 9 The figure is a diagram showing the wear amount of the thermal spray coating prepared in Examples 3 to 5 of the present invention and Comparative Example 1. Fig. 9 As shown in the figure, from the wear amount point of view, when the nickel-plated diamond particle size is 50 μm, the wear amount of the coating samples with 25 wt.% and 37.5wt.% is less than that with 50 wt.% particle size, but the mass loss of the 37.5wt.% grinding ball is greater.
[0074] Fig.10 : is the particle size distribution diagram of nickel-plated diamond in Examples 1 to 3 of the present invention. Fig.10 As shown, Fig.10 The median curve analysis shows that the median particle sizes of the nickel-plated diamonds in Examples 1 to 3 are 10.4 μm, 29.6 μm, and 55.4 μm, respectively.
[0075] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0076] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a nickel-based composite thermal spray coating, characterized in that: The following steps are involved: The nickel-plated diamond powder and the nickel-based alloy powder are mixed and ball-milled to obtain a spraying powder; The spray powder is thermally sprayed on the surface of a stainless steel workpiece substrate. During the thermal spraying process, the nickel-based alloy powder wraps the nickel-plated diamond during deposition and is deposited on the surface of the stainless steel workpiece substrate to obtain a nickel-based composite thermal spray coating.
2. The method for preparing the nickel-based composite thermal spray coating according to claim 1, characterized in that: In the nickel-based composite thermal spray coating, the content of nickel-plated diamond powder is 20 wt.% to 60 wt.%, and the remainder is nickel-based alloy powder, which is 100% in total.
3. The method for preparing the nickel-based composite thermal spray coating according to claim 1, characterized in that: The nickel-based alloy powder is Ni60 alloy powder.
4. The method for preparing the nickel-based composite thermal spray coating according to claim 1, characterized in that: The thermal spraying method adopts a high-speed fuel spraying process. The vertical distance between the stainless steel workpiece substrate and the nozzle is 200 mm to 300 mm. The propane gas pressure and the combustion-supporting air pressure are set to 1:1, the pressure is greater than 70 psi to 80 psi, the powder feeding gas pressure is 20 psi to 22 psi, and the powder feeding speed is 3 g / s to 5 g / s.
5. The method for preparing the nickel-based composite thermal spray coating according to claim 1, characterized in that: The particle size of the nickel-plated diamond powder is 5 μm to 60 μm, and the particle size of the nickel-based alloy powder is 30 μm to 100 μm.
6. The method for preparing the nickel-based composite thermal spray coating according to claim 1, characterized in that: The stainless steel workpiece substrate is pretreated before thermal spraying, including the following steps: after grinding and flattening the surface of the stainless steel workpiece substrate, sandblasting is performed to obtain a continuously undulating microscopic morphology structure, wherein the sandblasting medium in the sandblasting process is corundum.
7. The method for preparing the nickel-based composite thermal spray coating according to claim 1, characterized in that: The ball milling speed is 100 r / min~150 r / min, and the ball milling time is 6 h~9 h.
8. The method for preparing the nickel-based composite thermal spray coating according to claim 1, characterized in that: The stainless steel workpiece is 316 stainless steel.
9. A nickel-based composite thermal spray coating, characterized in that: The nickel-based composite thermal spray coating prepared by the preparation method according to any one of claims 1 to 9 has a thickness of 200 μm to 300 μm and a coating porosity of less than 1.5%.